Membangun karakter dan semangat belajar siswa dengan media LAGA - Rahmatullah, Agung; Kamila, Ihdia Uswah; Elzahira, Wilda (Maliki Interdisciplinary Journal, 2025)
LAGA (Lomba Adu Gesit Menangat Bendera) learning media is a creative innovation in the world of education designed to increase students' enthusiasm and activeness in learning. Through a competitive and fun group game approach, students not only learn to understand the subject matter, but also develop important skills such as communication, cooperation, and critical thinking. The simple LAGA implementation process using flags, answer bottles, and questions through digital media makes it easy to apply at various levels of education. In addition, this method also trains students courage to speak in public and answer questions quickly. Thus, LAGA is not only a learning medium, but also an effective and fun means of character building for students.